The implications of the agricultural holdings with legal entity when using the agricultural lands in Romania - Ioan Sebastian Brumă; Valentin-Mihai Bohatereţ (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
High-performance agriculture cannot be done in the absence of modern agricultural holdings, altogether holdings with a legal entity based on private property lands or those on lease, conceded or rented, which meet the agrotechnical request fit for each holding type. In this regard, the General Agricultural Censuses from 2002 and 2010 reveal a series of information that outline the manner in which the agricultural holdings with legal entity engage themselves in using the agricultural lands in Romania. Thus we notice holding groups distributed on size categories and how their holding structure is influenced by the usage category of the lands utilized and also by the geographical particularity of the region. Additionally, there is an improvement regarding the qualitative developments made in order to change the medium size of the agricultural holding with legal entity. The study identifies the current and perspective trends concerning the changes of agricultural holding (with legal entity) structure as effect of the direct relation between the agricultural holdings without legal entity and those with legal entity when using the agricultural lands in Romania.
Keywords: 330; agricultural holdings with legal entity; medium size of agricultural holding; the usage of lands; holding structures